(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Active learning is a kind of approach to education that is based upon the philosophy of the nature of the learning process. The active learning approach to education consists of guiding principles of teaching and learning. The central idea of this approach is that thought process is developed and concepts are constructed as a result of human activity and interaction. Therefore the aim of active learning is to provide the learner, the experiences which help in cognitive growth. The origin of active learning can be traced to mix up of applied psychology known as social cognitive constructivism concept given by the twentieth century educational philosopher John Dewey.Execution of active learning approach needs for a creative, constructivist and pragmatic principles, resulted into a very different organization of the classroom from the traditional and behaviourist principles. So these philosophical assumptions which define the desired outcome of education such as school program system learning processes and multiple aspects of operations and processes have been taken into considerations in this piece of research paper.